The association of air pollution in respiratory allergy: Its impact in an industrial city - de Lira-Quezada, Cindy Elizabeth; González-Díaz, Sandra Nora; Cotera-de Lira, Angel Gabriel; Macouzet-Sánchez, Carlos; Acuña-Ortega, Natalhie; Guzman-Avilán, Rosa Ivett; Macías-Weinmann, Alejandra (The World Allergy Organization journal, 2024)
Asthma and allergic diseases have increased in recent decades and are more common in industrialized countries. Industrial areas with a considerably high number of inhabitants and vehicles can favor the presence of serious air pollution and therefore the appearance and exacerbation of respiratory allergy symptoms. The objective of this study was to determine the relationship between exposure to environmental pollutants with exacerbation of respiratory allergy. A total of 240 subjects above 6 years old who lived in the metropolitan area of Monterrey, Nuevo León, Mexico, with diagnosis of allergic rhinitis and/or asthma, were included. The subject's address was registered in the database and the rhinitis control assessment test (RCAT) and the asthma control test (ACT) were applied. Environmental data were obtained from the Environmental Monitoring System (SIMA) of Nuevo León. Geolocation of industries and avenues in proximity of subject's addresses and SIMA stations were obtained through geographic information systems using ArcGis software. The relation between pollutants and subjects’ RCAT, ACT, and spirometry results in the 14 stations was established. PM10 and forced vital capacity (FVC) had an r = 0.074 with p = 0.005, PM10 and absolute FEV1/FVC ratio presented an r = −0.102 with a p = 0.000; The distance found to be associated with a worsening of respiratory symptoms was living 165 m from a main road or 241 m from an industrial establishment. Exposure to pollutants present in the environment are factors associated with increased symptoms in subjects with respiratory allergies.